Predictors of nurses' and midwives' intentions to provide maternal and child healthcare services to adolescents in South Africa. Issue 1 (December 2016) - Jonas, Kim; Reddy, Priscilla; van den Borne, Bart; Sewpaul, Ronel; Nyembezi, Anam; Naidoo, Pamela; Crutzen, Rik
Abstract Background Adolescent mothers are at a much higher risk for maternal mortality compared to mothers aged 20 years and above. Newborns born to adolescent mothers are also more likely to have low birth weight, with the risk of long-term effects such as early onset of adult diabetes than newborns of older mothers. Few studies have investigated the determinants of adequate quality maternal and child healthcare services to pregnant adolescents. This study was conducted to gain an understanding of nurses' and midwives' intentions to provide maternal and child healthcare and family planning services to adolescents in South Africa. Methods A total of 190 nurses and midwives completed a cross-sectional survey. The survey included components on demographics, knowledge of maternal and child healthcare (MCH) and family planning (FP) services, attitude towards family planning services, subjective norms regarding maternal and child healthcare and family planning services, self-efficacy with maternal and child healthcare and family planning services, and intentions to provide maternal and child healthcare and family planning services to adolescents. Pearson's correlation analysis was conducted to determine the association between knowledge, attitude, subjective norms, self-efficacy, and intention variables for FP and MCH services. A 2-step linear regression analysis was then conducted for both FP and MCH services to predict the intentions to provide FP and MCH services to adolescents. Results Self-efficacy to conduct MCH services (β = 0.55, p < 0.01) and years of experience as a nurse- midwife (β = 0.14, p < 0.05) were associated with stronger intentions to provide the services. Self-efficacy to provide FP services (β = 0.30, p < 0.01) was associated with stronger intentions to provide FP services. Conclusions Self-efficacy has a strong and positive association with the intentions to provide both MCH and FP services, while there is a moderate association with attitude and norms. There is a need to improve and strengthen nurses' and midwives' self-efficacy in conducting both MCH and FP services in order to improve the quality and utilization of the services by adolescents in South Africa.